Calvin's New Testament commentaries ; vol. 4 - Calvin, John, 1509-1564; Parker, T.H.L.; Torrance, David W.; Torrance, Thomas Forsyth, 1913- (Grand Rapids, MI Eerdmans, 1972)
Contents : v. 4 : The gospel according to St John 1-10. Includes bibliographical references and indexes.
Keywords: Bible. N.T. John I-X -- commentaries